INTERNATIONAL SALT COMPANY: DIVIDENDS OUT OF SUBSIDIARY SURPLUS AT DATE OF ACQUISITION; AMORTALIZATION OF BOND DISCOUNT. - Fisher, Allan J. (The Accounting Review, 1941)
The article discusses a case of International Salt Co. related to dividends out of subsidiary surplus at date of acquisition. An examination of the financial statements of the International Salt Co. from 1934 to date discloses two major points of interest, namely, a long-drawn-out controversy with the U.S. Securities and Exchange Commission as to the treatment of dividends received from subsidiaries, and a changing concept of the amortization of bond discount or premium. The International Salt Co. was incorporated in New Jersey on August 22, 1901, with a perpetual charter, and in 1934 was a holding company with six subsidiaries. While the correspondence files of the Securities and Exchange Commission may contain a plausible defense of the company's earlier position in refusing to classify these dividends as reductions in investments rather than as additions to income, on the basis of the disclosed information the demand of the Commission would appear to be entirely legitimate and in accordance with common accounting practice. Turning now to the second issue, the treatment of bond discount and premium by the International Salt Co. has undergone an interesting evolution. The treatment scarcely accords with generally accepted accounting practice.